Prevalence and associations of depression in orthopedic trauma patients at 4-weeks since admission: a prospective cohort study at a tertiary care center in Northern India - Kumar, Santosh; Verma, Vikas; Kushwaha, Umesh; Arya, Amit (Asian Journal of Medical Sciences, 2022)
Background: Depressive symptoms have been reported in admitted patients of musculoskeletal trauma. However, prevalence and associations of depression have not been reported after definitive management of injury. Aims and Objectives: The objectives of this study were to document the presence of depressive symptoms in adult musculoskeletal injury patients and identify factors associated with an abnormal score on the depression sub-scale of HADS at 4-weeks since admission. Materials and Methods: A longitudinal cohort study was undertaken on musculoskeletal injury patients admitted in the orthopedics department. Patients were enrolled on a randomly chosen day of the week. Subjects were excluded if they suffered from conditions known to preclude the assessment of the mental status. Age, sex, injury severity score, matrimonial status, insurance status, educational status, economic condition, support from family, alcohol abuse, and cannabis abuse were recorded at the time of admission. At 4-weeks after admission, enrolled subjects were screened for depression using the depression subscale of Hospital anxiety and depression scale score. Pain was recorded using visual analogue scale (VAS). Bivariate and multivariate analysis was used to identify predictors of an abnormal HADS score. Results: One-hundred ninety subjects were included. Average age of the subjects was 33.8 years. Thirty nine (21.53%) were females. At 4-weeks, 49 (25.79%) had an abnormal HADS score. A higher VAS score for pain, a younger age, living in a nuclear family and cannabis abuse were associated with an abnormal HADS score. Conclusion: Depressive symptoms are common in musculoskeletal injury patients at 4-weeks after admission.